Reconstruction of the mandibular condyle due to degenerative disease - Nicholas Wilken; Gary Warburton (Journal of Oral Biology and Craniofacial Research, 2023)
Degenerative joint disease (DJD), also known as osteoarthritis is the most common form of arthritis and can affect the temporomandibular joint (TMJ). TMJ DJD is characterized by degradation of the articular cartilage and synovial tissues resulting in characteristic morphologic changes in the underlying bone. DJD can occur at any age, but it is more common in older age groups. TMJ DJD may be unilateral or bilateral. The American Academy of Orofacial Pain categorizes TMJ DJD into primary and secondary types. Primary DJD is seen in the absence of any local or systemic factors and secondary DJD is associated with a prior traumatic event or disease process. Frequently, these patients present with pain and limited residual mandibular function resulting in significantly diminished quality of life. Classic radiographic features on orthopantogram and CT imaging include loss of joint space, osteophytes (bird-beak appearance of the condyle), subchondral cysts, erosions, flattening of the condylar head, bony resorption and/or heterotopic bone (Figure 1). Conservative and medical management is successful in the majority of patients until the active degenerative phase burns out, but some will progress to end stage joint disease and require reconstruction of the TMJ. Reconstruction of the mandibular condyle should be considered to restore mandibular function and form to patients who have lost it secondary to degenerative joint disease affecting the glenoid fossa/mandibular condyle unit.